Proceedings of the 5th International Conference on Accounting and Finance (ICAF 2019) 2019
DOI: 10.2991/icaf-19.2019.10
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis Of Fraud Pentagon Theory And Financial Distress For Detecting Fraudulent Financial Reporting In Banking Sector In Indonesia (Empirical Study Of Listed Banking Companies On Indonesia Stock Exchange In 2012-2017)

Abstract: This study aims to analyze the fraud pentagon theory and financial distress for detecting fraudulent financial reporting in banking companies in Indonesia listed on the Stock Exchange in 2012-2017. The sampling technique used purposive sampling with the sample of 30 companies. The hypothesis testing was done by testing multiple linear regression models which were processed using SPSS 15.0. The result shows that quality of external auditor has a positive effect on fraudulent financial reporting, change in audit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 11 publications
5
16
0
4
Order By: Relevance
“…This is because in top 100 companies, publication is mandatory, the company wants to show composition of the top management, so the number of photos of the management does not symbolize the arrogance of the management. This result in line with previous study by [14], [15] with got the same result.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This is because in top 100 companies, publication is mandatory, the company wants to show composition of the top management, so the number of photos of the management does not symbolize the arrogance of the management. This result in line with previous study by [14], [15] with got the same result.…”
Section: Resultssupporting
confidence: 92%
“…Ego (arrogance) is an attitude of superiority and greed of someone who believes that internal control does not affect him [14]. The number of CEO photos displayed in company's annual report represents the high level of arrogance of the CEO [15]. Research conducted by [11] shows that the frequent number of CEO's pictures has an effect in detecting financial statement.…”
Section: Effect Of Frequent Number Of Ceo's Picture In Detecting Fina...mentioning
confidence: 99%
“…So that the quality of external auditor does not significantly affect to the tendency of fraud of financial statements. Therefore, the finding contradicts with Akbar's study (2017), Ulfah et al (2017), Utami & Pusparini (2019). However, it is in line with several studies that found BIG cannot indicate the tendency of fraud of financial statement.…”
Section: Quality Of External Auditor and Fraud Of Financial Statementsmentioning
confidence: 56%
“…Kejadian kegagalan audit meningkat setelah perubahan auditor (Skousen et al, 2011). Hasil dari penelitian Utami & Pusparini (2019), Umar et al (2020)…”
Section: H3: Ineffective Monitoring Memiliki Pengaruh Dalam Mendeteks...unclassified